Determinants of Infant Young Child Feeding Among Mothers of Malnourished Children in South Punjab, Pakistan: A Qualitative Study - Ahmed, Farooq; Malik, Najma Iqbal; Shahzad, Muhammad; Ahmad, Manal; Shahid, Muhammad; Feng, Xing Lin; Guo, Jing (Frontiers in Public Health, 2022)
This study explored infant young child feeding (IYCF) beliefs and practices and deconstructed breastfeeding barriers among mothers of severely malnourished children. Using purposive sampling, a total of 20 lactating mothers were selected for semi-structured interviews in the most marginalized district of Punjab province of Pakistan. Results revealed that immediacy, exclusivity, frequency, and duration of breastfeeding were restricted owing to multiple social, cultural, and economic, determinants. Sociocultural barriers to exclusive breastfeeding included the introduction of various foods to infants such as pre-lacteal, butter, animal/formula milk by mothers or grandmothers, and perception of breastmilk’s composition as thin, impotent, and bad quality. Household circumstances, parents’ income, mothers’ diet and work burden, parental relationship and mental stress are other important economic and psychological barriers. Poor mothers reduced breastfeeding when work or fertility burden was high. Moreover, mothers breastfed female infants inadequately after birth. Some women became indifferent when they knew a female baby was growing in the belly. The colostrum was discarded based on a strange physical look. Birthing difficulties and ritual of prelacteal to transfer religion and culture delayed breastfeeding early initiation. Meanwhile, formula milk was recommended supplemented with the complaints by mothers against common weakness and insufficiency of breastmilk. Also, washing bottles with detergents was high. We concluded that poverty, maternal illiteracy, high work burden on women, limited dietary diversity in the household, and use of cow and bottled milk were the most significant reasons that might have affected infants’ health.